Analisis Hubungan Antara Penggunaan Musik dan Tingkat Konsentrasi Mahasiswa - Wulan Siti Nurjanah; Riantika Mutiara; Muhammad Al Ghifari; Mia Lasmi Wardiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the correlation between music-listening habits and students’ concentration levels during academic tasks. The research is motivated by the prevalent tendency among students to listen to music while studying, despite ongoing debates regarding its cognitive effects. Employing a quantitative research design, the study utilizes a survey method by distributing questionnaires to students across various academic disciplines. The collected data were analyzed using correlation techniques to examine the association between the frequency of music listening and levels of concentration. The results indicate a significant relationship between the type of music and students’ concentration, although the degree of impact varies based on the nature of the academic activity and individual preferences. These findings offer valuable insights for students and educational institutions in fostering more effective and supportive learning environments.